PENGARUH PEMBELAJARAN BIOLOGI BERBASIS STEAM TERINTEGRASI LITERASI SAINS TERHADAP KEMAMPUAN BERPIKIR KREATIF SISWA - Hilman Hadi; Nur'aini; Wawan Muliawan; Marhamah (Cocos Bio, 2024)
This study aims to determine the effect of STEAM-based biology learning integrated with science literacy on students' creative thinking skills. This type of research uses quasi-experimental design. The population of this study were all grade X students at MA Mu "allimin NWDI Pancor in the 2023/2024 academic year. The research sample was determined by Simple Random Sampling technique. Class X-B as an experimental class using the STEAM approach and class X-A as a control class using the lecture method. The research design used was Posttest-Only Control Design. Data collection techniques were carried out through creative thinking instruments. Data were analyzed using independent sample t test analysis. The hypothesis results show that tcount> ttable (3.525> 1.645) which means H0 is rejected and Ha is accepted.